An intravital microscopy-based approach to assess intestinal permeability and epithelial cell shedding performance - Martínez Sánchez, Luz del Carmen; Pradhan, Rashmita; Ngo, Phuong A.; Erkert, Lena; Becker, Lea; Watson, Alastair J.; Atreya, Imke; Neurath, Markus; Lopez Posadas, Rocío (Journal of Visualized Experiments, 2020)
Intravital microscopy of the gut using confocal imaging allows real time observation of epithelial cell shedding and barrier leakage in living animals. Therefore, the intestinal mucosa of anesthetized mice is topically stained with unspecific staining (acriflavine) and a fluorescent tracer (rhodamine-B dextran), mounted on a saline solution-rinsed plate and directly imaged using a confocal microscope. This technique can complement other non-invasive techniques to identify leakage of intestinal permeability, such as transmucosal passage of orally administered tracers. Besides this, the approach presented here allows the direct observation of cell shedding events at real-time. In combination with appropriate fluorescent reporter mice, this approach is suitable for shedding light into cellular and molecular mechanisms controlling intestinal epithelial cell extrusion, as well as to other biological processes. In the last decades, interesting studies using intravital microscopy have contributed to knowledge on endothelial permeability, immune cell gut homing, immune-epithelial communication and invasion of luminal components, among others. Together, the protocol presented here would not only help increase the understanding of mechanisms controlling epithelial cell extrusion, but could also be the basis for the developmental of other approaches to be used as instruments to visualize other highly dynamic cellular process, even in other tissues. Among technical limitations, optical properties of the specific tissue, as well as the selected imaging technology and microscope configuration, would in turn, determine the imaging working distance, and resolution of acquired images.
CRIS-Team Scopus Importer:2020-12-25

Anti-beta 7 integrin treatment impedes the recruitment on non-classical monocytes to the gut and delays macrophage-mediated intestinal wound healing - Sommer, Katrin; Heidbreder, Karin; Kreiß, Lucas; Dedden, Mark; Paap, Eva-Maria; Wiendl, Maximilian; Becker, Emily; Atreya, Raja; Müller, Tanja; Atreya, Imke; Waldner, Maximilian; Schürmann, Sebastian; et al. (Clinical and Translational Medicine, 2023)
BackgroundClosing mucosal defects to reach mucosal healing is an important goal of therapy in inflammatory bowel disease (IBD). Among other cells, monocyte-derived macrophages are centrally involved in such intestinal wound healing. We had previously demonstrated that the anti-alpha 4 beta 7 integrin antibody vedolizumab blocks the recruitment of non-classical monocytes as biased progenitors of wound healing macrophages to the gut and delays wound healing. However, although important for the interpretation of disappointing results in recent phase III trials in IBD, the effects of the anti-beta 7 antibody etrolizumab on wound healing are unclear so far. MethodsWe analyzed the expression of etrolizumab targets on human and mouse monocyte subsets by flow cytometry and assessed their function in adhesion and homing assays. We explored wound-associated monocyte recruitment dynamics with multi-photon microscopy and compared the effects of etrolizumab and vedolizumab surrogate (-s) antibodies on experimental wound healing and wound-associated macrophage abundance. Finally, we investigated wound healing macrophage signatures in the large intestinal transcriptome of patients with Crohn's disease treated with etrolizumab. ResultsHuman and mouse non-classical monocytes expressed more alpha E beta 7 integrin than classical monocytes and were a target of etrolizumab-s, which blocked non-classical monocyte adhesion to MAdCAM-1 and E-Cadherin as well as gut homing in vivo. Intestinal wound healing was delayed on treatment with etrolizumab-s along with a reduction of peri-lesional wound healing macrophages. Wound healing macrophage signatures in the colon of patients with Crohn's disease were substantially down-regulated on treatment with etrolizumab, but not with placebo. ConclusionsCombined blockade of alpha E beta 7 and alpha 4 beta 7 with etrolizumab seems to exceed the effect of anti-alpha 4 beta 7 treatment on intestinal wound healing, which might help to inform further investigations to understand the recent observations in the etrolizumab phase III trial program.
CRIS-Team WoS Importer:2023-05-05

ATP citrate lyase (ACLY)-dependent immunometabolism in mucosal T cells drives experimental colitis in vivo - Schulz-Kuhnt, Anja; Rühle, Katharina; Javidmehr, Asal; Döbrönti, Michael; Biwank, Jana; Knittel, Selina; Neidlinger, Peter; Leupold, Jannik; Liu, Lijuan; Dedden, Mark; Taudte, Regina Verena; Geßner, Arne; et al. (Gut, 2024)
Objective Mucosal T cells play a major role in inflammatory bowel disease (IBD). However, their immunometabolism during intestinal inflammation is poorly understood. Due to its impact on cellular metabolism and proinflammatory immune cell function, we here focus on the enzyme ATP citrate lyase (ACLY) in mucosal T cell immunometabolism and its relevance for IBD. Design ACLY expression and its immunometabolic impact on colitogenic T cell function were analysed in mucosal T cells from patients with IBD and in two experimental colitis models. Results ACLY was markedly expressed in colon tissue under steady-state conditions but was significantly downregulated in lamina propria mononuclear cells in experimental dextran sodium sulfate-induced colitis and in CD4+ and to a lesser extent in CD8+ T cells infiltrating the inflamed gut in patients with IBD. ACLY-deficient CD4+ T cells showed an impaired capacity to induce intestinal inflammation in a transfer colitis model as compared with wild-type T cells. Assessment of T cell immunometabolism revealed that ACLY deficiency dampened the production of IBD-relevant cytokines and impaired glycolytic ATP production but enriched metabolites involved in the biosynthesis of phospholipids and phosphatidylcholine. Interestingly, the short-chain fatty acid butyrate was identified as a potent suppressor of ACLY expression in T cells, while IL-36α and resolvin E1 induced ACLY levels. In a translational approach, in vivo administration of the butyrate prodrug tributyrin downregulated mucosal infiltration of ACLYhigh CD4+ T cells and ameliorated chronic colitis. Conclusion ACLY controls mucosal T cell immunometabolism and experimental colitis. Therapeutic modulation of ACLY expression in T cells emerges as a novel strategy to promote the resolution of intestinal inflammatio

Baseline levels of dynamic CD4+ T cell adhesion to MAdCAM-1 correlate with clinical response to vedolizumab treatment in ulcerative colitis: a cohort study - Allner, Clarissa; Melde, Michaela; Becker, Elisabeth; Fuchs, Friederike; Mühl, Laura; Klenske, Entcho; Müller, Lisa; Morgenstern, Nadine; Fietkau, Konstantin; Hirschmann, Simon; Atreya, Raja; Atreya, Imke; et al. (BMC Gastroenterology, 2020)
BACKGROUND: While the number of therapeutic options for treating inflammatory bowel diseases (IBD) is increasing, evidence for rational treatment decisions is scarce in many cases. In particular, appropriate biomarkers to predict the response to the anti-α4β7 integrin antibody vedolizumab are currently lacking. METHODS: We performed a cohort study with 21 patients suffering from ulcerative colitis (UC), in which first-time treatment with vedolizumab was initiated. CD4+ T cells were isolated from the peripheral blood and dynamic adhesion to recombinant mucosal vascular addressin cell adhesion molecule (MAdCAM-)1 in vitro as well as the effect of vedolizumab on such adhesion in vitro was determined. The expression of α4β1 integrin on peripheral blood CD4+ T cells was quantified by flow cytometry. Electronic patient records were reviewed to determine clinical response to vedolizumab. RESULTS: Dynamic adhesion of peripheral blood CD4+ T cells to MAdCAM-1 and the reduction of adhesion following vedolizumab treatment in vitro were higher and the change in α4β1 expression on CD4+ T cells was different in vedolizumab responders and non-responders. Responders could be identified with high specificity and positive-predictive value. CONCLUSIONS: Determining dynamic adhesion of CD4+ T cells to MAdCAM-1 and the in vitro response to vedolizumab before treatment initiation or dynamic integrin regulation in the early course of treatment seem to be promising tools to predict the clinical response to vedolizumab therapy. Larger prospective studies are warranted.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Adhesion; Gut homing; Inflammatory bowel diseases; T cells; Vedolizumab

Blocking GPR15 Counteracts Integrin-dependent T Cell Gut Homing in Vivo - Schramm, Sebastian; Liu, Lijuan; Saad, Marek; Dietz, Lisa; Dedden, Mark; Müller, Tanja; Atreya, Imke; Bosch-Voskens, Caroline; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (Journal of Crohns & Colitis, 2024)
Background and Aims: The G protein coupled receptor GPR15 is expressed on and functionally important for T cells homing to the large intestine. However, the precise mechanisms by which GPR15 controls gut homing have been unclear. Thus, we aimed to elucidate these mechanisms as well as to explore the potential of targeting GPR15 for interfering with T cell recruitment to the colon in inflammatory bowel disease [IBD]. Methods: We used dynamic adhesion and transmigration assays, as well as a humanised in vivo model of intestinal cell trafficking, to study GPR15-dependent effects on gut homing. Moreover, we analysed GPR15 and integrin expression in patients with and without IBD, cross-sectionally and longitudinally. Results: GPR15 controlled T cell adhesion to MAdCAM-1 and VCAM-1 upstream of α4β7 and α4β1 integrin, respectively. Consistently, high co-expression of these integrins with GPR15 was found on T cells from patients with IBD, and GPR15 also promoted T cell recruitment to the colon in humanised mice. Anti-GPR15 antibodies effectively blocked T cell gut homing in vitro and in vivo. In vitro data, as well as observations in a cohort of patients treated with vedolizumab, suggest that this might be more effective than inhibiting α4β7. Conclusions: GPR15 seems to have a broad, but organ-selective, impact on T cell trafficking and is therefore a promising target for future therapy of IBD. Further studies are needed.
CRIS-Team Scopus Importer:2024-08-16
Keywords: adhesion; GPR15; Inflammatory bowel disease; T cell homing; vedolizumab

Clinical experiences and predictors of success of treatment with vedolizumab in IBD patients: a cohort study - Mühl, Laura; Becker, Elisabeth; Müller, Tanja; Atreya, Raja; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (BMC Gastroenterology, 2021)
Background: Vedolizumab has become a standard treatment for the inflammatory bowel diseases ulcerative colitis (UC) and Crohn’s disease (CD). However, there is an ongoing debate on the ideal individual treatment algorithms and means to predict treatment response are not routinely established. Aims: We aimed to describe our experiences with vedolizumab at a large German tertiary referral center and to identify clinical predictors of success of vedolizumab treatment. Methods: We performed a retrospective single-center cohort study employing univariable and multivariable analyses as well as Kaplan–Meier analyses of persistence on treatment. Results: 36% and 35% of the patients with UC and CD, respectively, reached clinical remission after 17 weeks. Patients with lower clinical disease activity were more likely to achieve remission. The median persistence on treatment was 33 months for UC and 29 months for CD. Conclusion: Our study confirms that vedolizumab is an efficient option for the treatment of UC and CD. Clinical parameters of disease activity may help to predict the success of treatment.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Inflammatory bowel diseases; Real-world data; Vedolizumab

Differential Effects of Ontamalimab Versus Vedolizumab on Immune Cell Trafficking in Intestinal Inflammation and Inflammatory Bowel Disease - Schulze, Lisa; Becker, Emily; Dedden, Mark; Liu, Lijuan; Van Passen, Chiara; Mohamed Abdou, Mariam; Müller, Tanja; Wiendl, Maximilian; Ullrich, Karen; Atreya, Imke; Leppkes, Moritz; Ekici, Arif Bülent; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: The anti-MAdCAM-1 antibody ontamalimab demonstrated efficacy in a phase II trial in ulcerative colitis and results of early terminated phase III trials are pending, but its precise mechanisms of action are still unclear. Thus, we explored the mechanisms of action of ontamalimab and compared it to the anti-α4β7 antibody vedolizumab. Methods: We studied MAdCAM-1 expression with RNA sequencing and immunohistochemistry. The mechanisms of action of ontamalimab were assessed with fluorescence microscopy, dynamic adhesion and rolling assays. We performed in vivo cell trafficking studies in mice and compared ontamalimab and vedolizumab surrogate [-s] antibodies in experimental models of colitis and wound healing. We analysed immune cell infiltration under anti-MAdCAM-1 and anti-α4β7 treatment by single-cell transcriptomics and studied compensatory trafficking pathways. Results: MAdCAM-1 expression was increased in active inflammatory bowel disease. Binding of ontamalimab to MAdCAM-1 induced the internalization of the complex. Functionally, ontamalimab blocked T cell adhesion similar to vedolizumab, but also inhibited L-selectin-dependent rolling of innate and adaptive immune cells. Despite conserved mechanisms in mice, the impact of ontamalimab-s and vedolizumab-s on experimental colitis and wound healing was similar. Single-cell RNA sequencing demonstrated enrichment of ontamalimab-s-treated lamina propria cells in specific clusters, and in vitro experiments indicated that redundant adhesion pathways are active in these cells. Conclusions: Ontamalimab has unique and broader mechanisms of action compared to vedolizumab. However, this seems to be compensated for by redundant cell trafficking circuits and leads to similar preclinical efficacy of anti-α4β7 and anti-MAdCAM-1 treatment. These results will be important for the interpretation of pending phase III data.
CRIS-Team Scopus Importer:2023-12-15

Discrepant Phenotyping of Monocytes Based on CX3CR1 and CCR2 Using Fluorescent Reporters and Antibodies - Sommer, Katrin; Garibagaoglu, Hilal; Paap, Eva-Maria; Wiendl, Maximilian; Müller, Tanja; Atreya, Imke; Krönke, Gerhard; Neurath, Markus; Zundler, Sebastian (Cells, 2024)
Monocytes, as well as downstream macrophages and dendritic cells, are essential players in the immune system, fulfilling key roles in homeostasis as well as in inflammatory conditions. Conventionally, driven by studies on reporter models, mouse monocytes are categorized into a classical and a non-classical subset based on their inversely correlated surface expression of Ly6C/CCR2 and CX3CR1. Here, we aimed to challenge this concept by antibody staining and reporter mouse models. Therefore, we took advantage of Cx3cr1GFP and Ccr2RFP reporter mice, in which the respective gene was replaced by a fluorescent reporter protein gene. We analyzed the expression of CX3CR1 and CCR2 by flow cytometry using several validated fluorochrome-coupled antibodies and compared them with the reporter gene signal in these reporter mouse strains. Although we were able to validate the specificity of the fluorochrome-coupled flow cytometry antibodies, mouse Ly6Chigh classical and Ly6Clow non-classical monocytes showed no differences in CX3CR1 expression levels in the peripheral blood and spleen when stained with these antibodies. On the contrary, in Cx3cr1GFP reporter mice, we were able to reproduce the inverse correlation of the CX3CR1 reporter gene signal and Ly6C surface expression. Furthermore, differential CCR2 surface expression correlating with the expression of Ly6C was observed by antibody staining, but not in Ccr2RFP reporter mice. In conclusion, our data suggest that phenotyping strategies for mouse monocyte subsets should be carefully selected. In accordance with the literature, the suitability of CX3CR1 antibody staining is limited, whereas for CCR2, caution should be applied when using reporter mice.
CRIS-Team Scopus Importer:2024-05-31
Keywords: C-X3-C motif chemokine receptor 1 (CX3CR1); chemokine (C-C motif) receptor 2 (CCR2); classical monocytes; lymphocyte antigen 6C (Ly6C); non-classical monocytes

Editorial: Loss of Epithelial Barrier Integrity in Inflammatory Diseases: Cellular Mediators and Therapeutic Targets - Weidinger, Carl; Krug, Susanne M.; Voskens, Caroline; Moschen, Alexander R.; Atreya, Imke (Frontiers in Medicine, 2021)
CRIS-Team WoS Importer:2022-01-14

Engineering Therapeutic Regulatory T Cells to Overexpress G Protein-Coupled Receptor 15 Improves Functional Fitness for In Vivo Gut Homing - Müller, Tanja; Liu, Lijuan; Wiesinger, Manuel; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; Diefenbach, Andreas; et al. (Gastroenterology, 2025)
CRIS-Team Scopus Importer:2025-01-31

Epithelial RAC1-dependent cytoskeleton dynamics controls cell mechanics, cell shedding and barrier integrity in intestinal inflammation - Martínez Sánchez, Luz del Carmen; Phuong Anh Ngo,; Pradhan, Rashmita; Becker, Lukas S; Böhringer, David; Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Koch, Tatyana; Thonn, Veronika; Erkert, Lena; Stolzer, Iris; et al. (Gut, 2022)
Objective Increased apoptotic shedding has been linked to intestinal barrier dysfunction and development of inflammatory bowel diseases (IBD). In contrast, physiological cell shedding allows the renewal of the epithelial monolayer without compromising the barrier function. Here, we investigated the role of live cell extrusion in epithelial barrier alterations in IBD. Design Taking advantage of conditional GGTase and RAC1 knockout mice in intestinal epithelial cells (Pggt1b (i Delta IEC) and Rac1 (i Delta IEC) mice), intravital microscopy, immunostaining, mechanobiology, organoid techniques and RNA sequencing, we analysed cell shedding alterations within the intestinal epithelium. Moreover, we examined human gut tissue and intestinal organoids from patients with IBD for cell shedding alterations and RAC1 function. Results Epithelial Pggt1b deletion led to cytoskeleton rearrangement and tight junction redistribution, causing cell overcrowding due to arresting of cell shedding that finally resulted in epithelial leakage and spontaneous mucosal inflammation in the small and to a lesser extent in the large intestine. Both in vivo and in vitro studies (knockout mice, organoids) identified RAC1 as a GGTase target critically involved in prenylation-dependent cytoskeleton dynamics, cell mechanics and epithelial cell shedding. Moreover, inflamed areas of gut tissue from patients with IBD exhibited funnel-like structures, signs of arrested cell shedding and impaired RAC1 function. RAC1 inhibition in human intestinal organoids caused actin alterations compatible with arresting of cell shedding. Conclusion Impaired epithelial RAC1 function causes cell overcrowding and epithelial leakage thus inducing chronic intestinal inflammation. Epithelial RAC1 emerges as key regulator of cytoskeletal dynamics, cell mechanics and intestinal cell shedding. Modulation of RAC1 might be exploited for restoration of epithelial integrity in the gut of patients with IBD.
CRIS-Team WoS Importer:2022-03-25

Etrolizumab-s Does Not Induce Residual Trafficking of Regulatory T Cells - Schweda, Anna; Becker, Emily; Wiendl, Maximilian; Atreya, Raja; Atreya, Imke; Müller, Tanja; Neurath, Markus; Zundler, Sebastian (Inflammatory Bowel Diseases, 2022)
Background Blocking immune cell gut homing via α4β7 integrin with the monoclonal antibody vedolizumab is an established therapeutic strategy in inflammatory bowel disease. However, despite promising preclinical and phase 2 clinical data, the anti-β7 antibody etrolizumab yielded disappointing results in a large phase 3 trial program in UC. Mechanistic explanations are still lacking. We have recently shown that vedolizumab is associated with residual homing of regulatory T (Treg) cells in a certain exposure range and aimed to investigate whether a similar mechanism applies for etrolizumab. Methods We used flow cytometry, competitive dynamic adhesion, and transmigration assays to assess binding of the etrolizumab surrogate (etrolizumab-s) antibody FIB504 to Treg and effector T cells (Teff) and to explore the impact on cell trafficking. Results We observed only minimal differences in the binding of etrolizumab-s to Treg and Teff cells. Dynamic adhesion and transmigration of Treg and Teff cells was not substantially differentially affected at relevant concentrations. The β1+ and PI16+ Treg cells were only resistant to etrolizumab-s at low concentrations. Conclusions Etrolizumab does not seem to induce notable residual trafficking of Treg cells. Thus, the Teff overweight in the inflamed gut might persist despite reduced overall T cell recruitment. This might be one piece of the puzzle to explain recent clinical results in phase 3.
CRIS-Team WoS Importer:2022-07-22

Etrolizumab-s fails to control E-Cadherin-dependent co-stimulation of highly activated cytotoxic T cells - Wiendl, Maximilian; Dedden, Mark; Liu, Lijuan; Schweda, Anna; Paap, Eva-Maria; Ullrich, Karen; Hartmann, Leonie; Wieser, Luisa; Vitali, Francesco; Atreya, Imke; Müller, Tanja; Günther, Claudia; et al. (Nature Communications, 2024)
Despite promising preclinical and earlier clinical data, a recent phase III trial on the anti-β7 integrin antibody etrolizumab in Crohn’s disease (CD) did not reach its primary endpoint. The mechanisms leading to this outcome are not well understood. Here we characterize the β7+ T cell compartment from patients with CD in comparison to cells from individuals without inflammatory bowel disease. By flow cytometric, transcriptomic and functional profiling of circulating T cells, we find that triple-integrin-expressing (α4+β7+β1hi) T cells have the potential to home to the gut despite α4β7 blockade and have a specific cytotoxic signature. A subset of triple-integrin-expressing cells readily acquires αE expression and could be co-stimulated via E-Cadherin-αEβ7 interactions in vitro. Etrolizumab-s fails to block such αEβ7 signalling at high levels of T cell stimulation. Consistently, in CD patients treated with etrolizumab, T cell activation correlates with cytotoxic signatures. Collectively, our findings might add one important piece to the puzzle to explain phase III trial results with etrolizumab, while they also highlight that αEβ7 remains an interesting target for future therapeutic approaches in inflammatory bowel disease.
CRIS-Team Scopus Importer:2024-02-16

Expression and function of α4β7 integrin predict the success of vedolizumab treatment in inflammatory bowel disease - Schneider, Ines; Allner, Clarissa; Mühl, Laura; Melde, Michaela; Lissner, Donata; Mantzivi, Eleni; Glauben, Rainer; Vitali, Francesco; Becker, Emily; Atreya, Imke; Müller, Tanja; Atreya, Raja; et al. (Translational Research, 2022)
Inflammatory bowel diseases are medically intractable and require constant therapy in many cases. While a growing number of biologicals and small molecules is available for treatment, a substantial portion of patients experiences primary non-response to these compounds and head-to-head evidence for therapy selection is scarce. Thus, approaches to predict treatment success in individual patients are a huge unmet need. We had previously suggested that the expression and function of α4β7 integrin on T cells in the peripheral blood correlate to outcomes of therapy with the anti-α4β7 integrin antibody vedolizumab. Here, we conducted a translational multicenter trial to prospectively evaluate this hypothesis. In a cohort of 89 patients with inflammatory bowel disease undergoing regular therapy with vedolizumab, lower baseline expression of α4β7 was associated with short-term clinical response. Consistently, low α4β7 expression in patients achieving remission predicted sustained remission in week 30. Moreover, high dynamic adhesion of CD4+ T cells to MAdCAM-1 and high reduction of adhesion by vedolizumab in vitro at baseline were associated with clinical remission. These data substantiate the potential of α4β7 integrin function and expression to forecast outcomes of vedolizumab therapy. Further translational efforts are necessary to improve the performance of the assays and to implement the concept in clinical practice.
CRIS-Team Scopus Importer:2023-01-31

Functional Contribution and Targeted Migration of Group-2 Innate Lymphoid Cells in Inflammatory Lung Diseases: Being at the Right Place at the Right Time - Wirtz, Stefan; Schulz-Kuhnt, Anja; Neurath, Markus; Atreya, Imke (Frontiers in Immunology, 2021)
During the last decade, group-2 innate lymphoid cells (ILC2s) have been discovered and successfully established as crucial mediators of lung allergy, airway inflammation and fibrosis, thus affecting the pathogenesis and clinical course of many respiratory diseases, like for instance asthma, cystic fibrosis and chronic rhinosinusitis. As an important regulatory component in this context, the local pulmonary milieu at inflammatory tissue sites does not only determine the activation status of lung-infiltrating ILC2s, but also influences their motility and migratory behavior. In general, many data collected in recent murine and human studies argued against the former concept of a very strict tissue residency of innate lymphoid cells (ILCs) and instead pointed to a context-dependent homing capacity of peripheral blood ILC precursors and the inflammation-dependent capacity of specific ILC subsets for interorgan trafficking. In this review article, we provide a comprehensive overview of the so far described molecular mechanisms underlying the pulmonary migration of ILC2s and thereby the numeric regulation of local ILC2 pools at inflamed or fibrotic pulmonary tissue sites and discuss their potential to serve as innovative therapeutic targets in the treatment of inflammatory lung diseases.
CRIS-Team WoS Importer:2021-07-09

How the Tumor Micromilieu Modulates the Recruitment and Activation of Colorectal Cancer-Infiltrating Lymphocytes - Atreya, Imke; Neurath, Markus (Biomedicines, 2022)
The successful treatment of advanced colorectal cancer disease still represents an insufficiently solved clinical challenge, which is further complicated by the fact that the majority of malignant colon tumors show only relatively low immunogenicity and therefore have only limited responsiveness to immunotherapeutic approaches, such as, for instance, the use of checkpoint inhibitors. As it has been well established over the past two decades that the local tumor microenvironment and, in particular, the quantity, quality, and activation status of intratumoral immune cells critically influence the clinical prognosis of patients diagnosed with colorectal cancer and their individual benefits from immunotherapy, the enhancement of the intratumoral accumulation of cytolytic effector T lymphocytes and other cellular mediators of the antitumor immune response has emerged as a targeted objective. For the future identification and clinical validation of novel therapeutic target structures, it will thus be essential to further decipher the molecular mechanisms and cellular interactions in the intestinal tumor microenvironment, which are crucially involved in immune cell recruitment and activation. In this context, our review article aims at providing an overview of the key chemokines and cytokines whose presence in the tumor micromilieu relevantly modulates the numeric composition and antitumor capacity of tumor-infiltrating lymphocytes.
CRIS-Team WoS Importer:2022-12-23

IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells. - Ullrich, Karen; Derdau, Julia; Baltes, Carsten; Battistella, Alice; Rosso, Gonzalo; Uderhardt, Stefan; Schulze, Lisa; Liu, Lijuan; Dedden, Mark; Spocinska, Marta; Kainka, Lucina; Kubánková, Markéta; et al. (Gut, 2023)
IL-3 has been reported to be involved in various inflammatory disorders, but its role in inflammatory bowel disease (IBD) has not been addressed so far. Here, we determined IL-3 expression in samples from patients with IBD and studied the impact of Il3 or Il3r deficiency on T cell-dependent experimental colitis. We explored the mechanical, cytoskeletal and migratory properties of Il3r -/- and Il3r +/+ T cells using real-time deformability cytometry, atomic force microscopy, scanning electron microscopy, fluorescence recovery after photobleaching and in vitro and in vivo cell trafficking assays. We observed that, in patients with IBD, the levels of IL-3 in the inflamed mucosa were increased. In vivo, experimental chronic colitis on T cell transfer was exacerbated in the absence of Il-3 or Il-3r signalling. This was attributable to Il-3r signalling-induced changes in kinase phosphorylation and actin cytoskeleton structure, resulting in increased mechanical deformability and enhanced egress of Tregs from the inflamed colon mucosa. Similarly, IL-3 controlled mechanobiology in human Tregs and was associated with increased mucosal Treg abundance in patients with IBD. Collectively, our data reveal that IL-3 signaling exerts an important regulatory role at the interface of biophysical and migratory T cell features in intestinal inflammation and suggest that this might be an interesting target for future intervention.
EVALuna2:539503

ILC2 Lung-Homing in Cystic Fibrosis Patients: Functional Involvement of CCR6 and Impact on Respiratory Failure - Schulz-Kuhnt, Anja; Greif, Vicky; Hildner, Kai; Knipfer, Lisa; Döbrönti, Michael; Zirlik, Sabine; Fuchs, Florian; Atreya, Raja; Zundler, Sebastian; Lopez Posadas, Rocío; Neufert, Clemens; Ramming, Andreas; et al. (Frontiers in Immunology, 2020)
Cystic fibrosis patients suffer from a progressive, often fatal lung disease, which is based on a complex interplay between chronic infections, locally accumulating immune cells and pulmonary tissue remodeling. Although group-2 innate lymphoid cells (ILC2s) act as crucial initiators of lung inflammation, our understanding of their involvement in the pathogenesis of cystic fibrosis remains incomplete. Here we report a marked decrease of circulating CCR6+ ILC2s in the blood of cystic fibrosis patients, which significantly correlated with high disease severity and advanced pulmonary failure, strongly implicating increased ILC2 homing from the peripheral blood to the chronically inflamed lung tissue in cystic fibrosis patients. On a functional level, the CCR6 ligand CCL20 was identified as potent promoter of lung-directed ILC2 migration upon inflammatory conditions in vitro and in vivo using a new humanized mouse model with light-sheet fluorescence microscopic visualization of lung-accumulated human ILC2s. In the lung, blood-derived human ILC2s were able to augment local eosinophil and neutrophil accumulation and induced a marked upregulation of pulmonary type-VI collagen expression. Studies in primary human lung fibroblasts additionally revealed ILC2-derived IL-4 and IL-13 as important mediators of this type-VI collagen-inducing effect. Taken together, the here acquired results suggest that pathologically increased CCL20 levels in cystic fibrosis airways induce CCR6-mediated lung homing of circulating human ILC2s. Subsequent ILC2 activation then triggers local production of type-VI collagen and might thereby drive extracellular matrix remodeling potentially influencing pulmonary tissue destruction in cystic fibrosis patients. Thus, modulating the lung homing capacity of circulating ILC2s and their local effector functions opens new therapeutic avenues for cystic fibrosis treatment.
CRIS-Team Scopus Importer:2020-06-02
Keywords: CCR6; cystic fibrosis; group-2 innate lymphoid cells; tissue remodeling; type-VI collagen

Increased Motility and Suppression of Ex Vivo–Expanded Regulatory T Cells Designed for Adoptive Transfer Therapy in Ulcerative Colitis - Müller, Tanja; Liu, Lijuan; Czerwinski, Tina; Wiesinger, Manuel; Dedden, Mark; Paap, Eva-Maria; Ullrich, Karen; Atreya, Imke; Siegmund, Britta; Atreya, Raja; Fabry, Ben; Berking, Carola; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2023)
CRIS-Team Scopus Importer:2023-06-02

Innate Lymphoid Cells as Regulators of Epithelial Integrity: Therapeutic Implications for Inflammatory Bowel Diseases - Schulz-Kuhnt, Anja; Neurath, Markus; Wirtz, Stefan; Atreya, Imke (Frontiers in Medicine, 2021)
The occurrence of epithelial defects in the gut relevantly contributes to the pathogenesis of inflammatory bowel diseases (IBD), whereby the impairment of intestinal epithelial barrier integrity seems to represent a primary trigger as well as a disease amplifying consequence of the chronic inflammatory process. Besides epithelial cell intrinsic factors, accumulated and overwhelmingly activated immune cells and their secretome have been identified as critical modulators of the pathologically altered intestinal epithelial cell (IEC) function in IBD. In this context, over the last 10 years increasing levels of attention have been paid to the group of innate lymphoid cells (ILCs). This is in particular due to a preferential location of these rather newly described innate immune cells in close proximity to mucosal barriers, their profound capacity to secrete effector cytokines and their numerical and functional alteration under chronic inflammatory conditions. Aiming on a comprehensive and updated summary of our current understanding of the bidirectional mucosal crosstalk between ILCs and IECs, this review article will in particular focus on the potential capacity of gut infiltrating type-1, type-2, and type-3 helper ILCs (ILC1s, ILC2s, and ILC3s, respectively) to impact on the survival, differentiation, and barrier function of IECs. Based on data acquired in IBD patients or in experimental models of colitis, we will discuss whether the different ILC subgroups could serve as potential therapeutic targets for maintenance of epithelial integrity and/or mucosal healing in IBD.
CRIS-Team Scopus Importer:2021-04-23
Keywords: colitis; cytokines; ILC plasticity; inflammatory bowel diseases; innate lymphoid cells; intestinal epithelium

Limited Dose-Dependent Effects of Vedolizumab on Various Leukocyte Subsets - Becker, Emily; Schweda, Anna; Ullrich, Karen; Voskens, Caroline; Atreya, Raja; Müller, Tanja; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Clinical and Translational Gastroenterology, 2022)
OBJECTIVES: The anti-α4β7 integrin antibody vedolizumab (VDZ) is successfully used for the treatment of inflammatory bowel diseases. However, only a subgroup of patients respond to therapy. VDZ is administered at a fixed dose, leading to a wide range of serum concentrations in patients. Previous work from our group showed a dose-dependent preferential binding of VDZ to effector compared with regulatory CD4 + T cells. Therefore, we aimed to determine the dose-dependent binding profile of VDZ to other leukocyte subsets. METHODS: We characterized α4β7 integrin expression on CD8 + T cells, CD19 + B cells, CD14 + monocytes, natural killer cells, and eosinophils from patients with inflammatory bowel disease and healthy controls. We studied the binding of VDZ to these cells at different concentrations and investigated the functional consequences for dynamic adhesion and transmigration in vitro . RESULTS: The expression of α4β7 differed between the analyzed leukocyte subsets and was significantly higher on eosinophils from inflammatory bowel disease patients compared with controls. Almost all α4β7-expressing cells from these subsets were bound by VDZ at a concentration of 10 μg/mL. Dynamic cell adhesion was significantly impaired in all subsets, but there were no dose-dependent differences in the inhibition of adhesion. DISCUSSION: Our data suggest that α4β7-expressing CD8 + T cells, CD19 + B cells, CD14 + monocytes, natural killer cells, and eosinophils are a target of VDZ. However, there do not seem to be concentration-dependent differences, regarding the effects on these cells in the clinically relevant range. Thus, the reported exposure-efficacy characteristic of VDZ can probably mainly be attributed to CD4 + T-cell subsets.
CRIS-Team Scopus Importer:2022-07-08

Linking IL-10 signaling with lipid metabolic programs in macrophages: dysregulated ceramide homeostasis drives colitis - Atreya, Imke; Neurath, Markus (Signal Transduction and Targeted Therapy, 2024)
CRIS-Team Scopus Importer:2024-06-21

Nr4a1-dependent non-classical monocytes are important for macrophage-mediated wound healing in the large intestine - Heidbreder, Karin; Sommer, Katrin; Wiendl, Maximilian; Müller, Tanja; Atreya, Imke; Hildner, Kai; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2023)
Introduction: Macrophages play an important role in intestinal wound healing. However, the trajectories from circulating monocytes to gut macrophages are incompletely understood. Methods: Taking advantage of mice depleted for non-classical monocytes due to deficiency for the transcription factor Nr4a1, we addressed the relevance of non-classical monocytes for large intestinal wound healing using flow cytometry, in vivo wound healing assays and immunofluorescence. Results: We show that wound healing in Nr4a1-deficient mice is substantially delayed and associated with reduced peri-lesional presence of macrophages with a wound healing phenotype. Discussion: Our data suggest that non-classical monocytes are biased towards wound healing macrophages. These insights might help to understand, how targeting monocyte recruitment to the intestine can be used to modulate intestinal macrophage functions.
CRIS-Team Scopus Importer:2023-02-10
Keywords: gut homing; intestinal wound healing; macrophages; monocytes; Nr4a1 (Nur77)

Regulation of Human Innate Lymphoid Cells in the Context of Mucosal Inflammation - Schulz-Kuhnt, Anja; Wirtz, Stefan; Neurath, Markus; Atreya, Imke (Frontiers in Immunology, 2020)
Since their identification as a unique cell population, innate lymphoid cells (ILCs) have revolutionized our understanding of immune responses, leaving their impact on multiple inflammatory and fibrotic pathologies without doubt. Thus, a tightly controlled regulation of local ILC numbers and their activity is of crucial importance. Even though this has been extensively studied in murine ILCs in the last few years, our knowledge of human ILCs is still lagging behind. Our review article will therefore summarize recent insights into the function of human ILCs and will particularly focus on their regulation under inflammatory conditions. The quality and intensity of ILC involvement into local immune responses at mucosal sites of the human body can potentially be modulated via three different axes: (1) activation of tissue-resident mature ILCs, (2) plasticity and local transdifferentiation of specific ILC subsets, and (3) tissue migration and accumulation of peripheral ILCs. Despite a still ongoing scientific effort in this field, already existing data on the fate of human ILCs under different pathologic conditions clearly indicate that all three of these mechanisms are of relevance for the clinical course of chronic inflammatory and autoimmune diseases and might likewise provide new target structures for future therapeutic strategies.
CRIS-Team Scopus Importer:2020-07-17
Keywords: cytokine; human immune system; ILC plasticity; innate lymphoid cells; mucosal inflammation; tissue migration

Residual homing of alpha 4 beta 7-expressing beta 1(+)PI16(+) regulatory T cells with potent suppressive activity correlates with exposure-efficacy of vedolizumab - Becker, Emily; Dedden, Mark; Gall, Christine; Wiendl, Maximilian; Ekici, Arif Bülent; Schulz-Kuhnt, Anja; Schweda, Anna; Bosch-Voskens, Caroline; Hegazy, Ahmed; Vitali, Francesco; Atreya, Raja; Müller, Tanja; et al. (Gut, 2021)
Objective The anti-alpha 4 beta 7 integrin antibody vedolizumab is administered at a fixed dose for the treatment of IBDs. This leads to a wide range of serum concentrations in patients and previous studies had suggested that highest exposure levels are associated with suboptimal clinical response. We aimed to determine the mechanisms underlying these non-linear exposure-efficacy characteristics of vedolizumab. Design We characterised over 500 samples from more than 300 subjects. We studied the binding of vedolizumab to T cells and investigated the functional consequences for dynamic adhesion, transmigration, gut homing and free binding sites in vivo. Employing single-cell RNA sequencing, we characterised alpha 4 beta 7 integrin-expressing T cell populations 'resistant' to vedolizumab and validated our findings in vitro and in samples from vedolizumab-treated patients with IBD. We also correlated our findings with a post-hoc analysis of the Gemini II and III studies. Results Regulatory T (T-Reg) cells exhibited a right-shifted vedolizumab binding profile compared with effector T (T-Eff) cells. Consistently, in a certain concentration range, the residual adhesion, transmigration, homing of and availability of functional alpha 4 beta 7 on T-Reg cells in vivo was higher than that of/on T-Eff cells. We identified a vedolizumab-'resistant' alpha 4 beta 7-expressing beta 1(+)PI16(+) T-Reg cell subset with pronounced regulatory properties as the substrate for this effect. Our observations correlated with exposure-efficacy data from Gemini II and III trials. Conclusion Completely blocking T-Eff cell trafficking with vedolizumab, while simultaneously permitting residual homing of powerful T-Reg cells in an optimal 'therapeutic window' based on target exposure levels might be a strategy to optimise treatment outcomes in patients with IBD.
CRIS-Team WoS Importer:2021-12-10

Spatial Single Cell Profiling Using Imaging Mass Cytometry: Inflammatory Versus Penetrating Crohn's Disease - Lehmann, Malte; Weixler, Benjamin; Elezkurtaj, Sefer; Loddenkemper, Christopher; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Fistula formation is a major complication in Crohn's disease [CD] and the role of the immune cell compartment remains to be elucidated. Thus, we compared the immune cell compartment of CD fistula to inflammatory CD colitis using imaging mass cytometry [IMC] and immunofluorescence. Methods: A 36-marker panel including structural, functional, and lineage markers for use in IMC was established. This panel was applied to analyse paraffin-embedded CD fistula tract [n = 11], CD colitis [n = 10], and colon samples from non-inflamed controls [n = 12]. Computational methods for cell segmentation, dimensionality reduction, and cell type clustering were used to define cell populations for cell frequency, marker distribution, and spatial neighbourhood analysis. Multiplex immunofluorescence was used for higher resolution spatial analysis. Results: Analysis of cell frequencies in CD fistulas compared to CD colitis and control colonic samples revealed a significant increase in neutrophils, effector cytotoxic T cells, and inflammatory macrophages in CD fistula samples, whereas regulatory T cells were decreased. Neutrophils in CD fistula expressed significantly more matrix metalloproteinase 9 [MMP9], correlating with extracellular matrix remodelling. Neighbourhood analysis revealed a strong association between MMP9+ neutrophils and effector cytotoxic T cells in both CD fistulas and colitis. Conclusions: This study presents the first highly multiplexed single cell analysis of the immune cell compartment of CD fistulas and their spatial context. It links immune cell dynamics, particularly MMP9+ neutrophils, to extracellular matrix remodelling in CD fistulas, offering insights into the complex network of cellular interactions and potential therapeutic targets for CD complications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: fistula; imaging mass cytometry; Penetrating Crohn's disease

Targeted inhibition of the WEE1 kinase as a novel therapeutic strategy in neuroendocrine neoplasms - Weindl, Lena; Atreya, Imke; Dietrich, Peter; Neubeck, Sabine; Neurath, Markus; Pavel, Marianne Ellen (Endocrine-Related Cancer, 2021)
Neuroendocrine neoplasms (NENs) represent a rare and heterogeneous group of malignancies, sharing features of both neural and endocrine cells. NENs G3 appear as a highly aggressive subset with a poor prognosis and limited therapeutic options. The small-molecule inhibitor of the WEE1 tyrosine kinase, adavosertib (AZD1775), has previously demonstrated potent anti-tumor effects on various types of cancer in preclinical and clinical studies. However, the role of adavosertib in NENs G3 had remained elusive. We evaluated the effects of adavosertib on pancreatic (BON-1, QGP-1) and bronchopulmonary (NCI-H720) neuroendocrine tumor cell lines applying 2D and 3D spheroid models. We newly demonstrated that adavosertib is sufficient to reduce cell viability and proliferation in neuroendocrine cell lines with features of high-grade NENs. As underlying mechanisms, we identified adavosertib-mediated DNA double-strand breaks and a G2/M cell cycle checkpoint abrogation leading into mitotic catastrophe and cancer cell apoptosis. Silencing of WEE1 via siRNA transfection resulted in a phenotype similar to adavosertib treatment. Together, inhibition of the WEE1 tyrosine kinase applying adavosertib on NENs G3 outlines a promising novel therapeutic strategy.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D cell culture; Cell cycle; G3; Neuroendocrine neoplasm; WEE1

The TLR9 agonist cobitolimod induces IL10 producing wound healing macrophages and regulatory T cells in ulcerative colitis - Schmitt, Heike; Ulmschneider, Julia; Billmeier, Ulrike; Scarozza, Patrizio; Sonnewald, Sophia; Reid, Stephen; Atreya, Imke; Rath, Timo; Zundler, Sebastian; Langheinrich, Melanie; Schüttler, Jürgen; Hartmann, Arndt; et al. (Journal of Crohns & Colitis, 2020)
BACKGROUND AND AIMS: The topically applied Toll-like receptor 9 (TLR9) agonist cobitolimod is a first-in-class DNA-based oligonucleotide that demonstrated therapeutic efficacy in clinical trials with ulcerative colitis (UC) patients. We here characterized its anti-inflammatory mechanism in UC. METHODS: Luminal cobitolimod administration was evaluated in an experimental DSS-induced colitis model. Cultured blood and mucosal cells from UC patients were treated with cobitolimod and analyzed via microarray, qRT-PCR, ELISA and flow cytometry. Intestinal slides of cobitolimod treated UC patients were analyzed by immunohistochemistry. RESULTS: Cobitolimod administration markedly suppressed experimental colitis activity and microarrays analyses demonstrated mucosal IL10 upregulation and suppression of IL17 signaling pathways. Cobitolimod treatment was associated with significant induction of mucosal IL10+ Tr1 and Treg cells and suppression of Th17 cells. TLR9 knockout mice indicated that cobitolimod requires TLR9 signaling for IL10 induction. In UC patients, mucosal TLR9 levels correlated with severity of inflammation. Cobitolimod inhibited IL17A and IL17F, but increased IL10 and FoxP3 expression in cultured intestinal UC T cells. Cobitolimod-mediated suppression of intestinal IL17+ T cells was abrogated by IL10 blockade. Furthermore, cobitolimod led to heightened IL10 production by wound healing macrophages. Immunohistochemistry in intestinal biopsies of cobitolimod treated UC patients indicated increased presence of IL10+ mononuclear and regulatory T cells, as well as reduction of IL17+ cells. CONCLUSION: Our studies suggest that activation of TLR9 via cobitolimod might represent a novel therapeutic approach in UC, as it suppresses Th17 cells and induces anti-inflammatory IL10+ macrophages and regulatory T cells, thereby modifying the dysregulated intestinal cytokine balance.
EVALuna2:212910
Keywords: Ulcerative colitis; TLR9; cobitolimod

Transcriptomes of MPO-deficient patients with generalized pustular psoriasis reveals expansion of CD4+cytotoxic T cells and an involvement of complement system and interferon pathways - Hüffmeier, Ulrike; Frey, Benjamin; Becker, Ina; Atreya, Imke; Berking, Carola; Moessner, R.; Wilsmann-Theis, D.; Uebe, Steffen; Kirchner, P.; Haskamp, Stefan (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-05

Transcriptomes of MPO-Deficient Patients with Generalized Pustular Psoriasis Reveals Expansion of CD4+ Cytotoxic T Cells and an Involvement of the Complement System - Haskamp, Stefan; Frey, Benjamin; Becker, Ina; Schulz-Kuhnt, Anja; Atreya, Imke; Berking, Carola; Pauli, David; Ekici, Arif Bülent; Berges, Johannes; Mößner, Rotraut; Wilsmann-Theis, Dagmar; Sticherling, Michael; et al. (Journal of Investigative Dermatology, 2022)
Generalized pustular psoriasis is a severe psoriatic subtype characterized by epidermal neutrophil infiltration. Although variants in IL36RN and MPO have been shown to affect immune cells, a systematic analysis of neutrophils and PBMC subsets and their differential gene expression dependent on MPO genotypes was not performed yet. We assessed the transcriptomes of MPO-deficient patients using single-cell RNA sequencing of PBMCs and RNA sequencing of neutrophils in a stable disease state. Cell-type annotation by multimodal reference mapping of single-cell RNA-sequencing data was verified by flow cytometry of surface and intracellular markers; the proportions of CD4+ cytotoxic T lymphocytes and other CD4+ effector cells were increased in generalized pustular psoriasis, whereas the frequencies of naïve CD4+ T cells were significantly lower. The expression of FGFBP2 marking CD4+ cytotoxic T lymphocytes and CD8+ effector memory T cells was elevated in patients with generalized pustular psoriasis with disease-contributing variants compared with that in noncarriers (P = 0.0015). In neutrophils, differentially expressed genes were significantly enriched in genes of the classical complement activation pathway. Future studies assessing affected cell types and pathways will show their contribution to generalized pustular psoriasis's pathogenesis and indicate whether findings can be transferred to the acute epidermal situation and whether depletion or inactivation of CD4+ cytotoxic T lymphocytes may be a reasonable therapeutic approach.
CRIS-Team Scopus Importer:2022-07-08

Vedolizumab blocks alpha 4 beta 7 integrin-mediated T cell adhesion to MAdCAM-1 in microscopic colitis - Besendorf, Laura; Müller, Tanja; Geppert, Carol-Immanuel; Schneider, Ines; Mühl, Laura; Atreya, Imke; Vitali, Francesco; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (Therapeutic Advances in Gastroenterology, 2022)
Background: In Crohn's disease and ulcerative colitis, the anti-alpha 4 beta 7 integrin antibody vedolizumab has demonstrated efficacy in phase III trials and has been successfully used under real-world conditions. Occasionally, it has also been used in other forms of inflammatory bowel disease (IBD) such as microscopic colitis (MC). However, the mechanisms of vedolizumab in MC have not been studied to date. Therefore, we aimed to investigate the expression and functional role of gut-homing integrins and in particular alpha 4 beta 7 integrin in a cohort study in MC.
CRIS-Team WoS Importer:2022-07-08
Keywords: α4β7 integrin; microscopic colitis; T cell trafficking; vedolizumab

α4β7 integrin-dependent adhesion of T cells to MAdCAM-1 is blocked by vedolizumab in patients with chronic refractory pouchitis - Melde, Michaela; Müller, Tanja; Schneider, Ignaz Hans Friedrich; Geppert, Carol-Immanuel; Mühl, Laura; Besendorf, Laura; Allner, Clarissa; Becker, Emily; Atreya, Imke; Vitali, Francesco; Atreya, Raja; Neurath, Markus; et al. (Therapeutic Advances in Gastroenterology, 2021)
Background: The anti-α4β7 integrin antibody vedolizumab is an established therapeutic option for the treatment of inflammatory bowel disease (IBD). It has also been successfully used in patients with chronic antibiotic-refractory pouchitis following proctocolectomey with ileal pouch-anal anastomosis. However, the expression and function of gut-homing markers as well as strategies to predict the response to vedolizumab in pouchitis are understudied so far. Methods: We used flow cytometry and dynamic adhesion assays to study the expression and function of gut-homing integrins on T cells from patients with pouchitis and controls as well as longitudinally during therapy of pouchitis with vedolizumab. Moreover, we describe clinical effects of vedolizumab in a cohort of patients with pouchitis. Results: T cells from patients with pouchitis express a specific profile of gut-homing integrins. Integrin α4β7 on T cells from patients with pouchitis mediates adhesion to mucosal addressin cell adhesion molecule (MAdCAM)-1, which can be blocked by vedolizumab in vitro. Vedolizumab efficiently treats pouchitis in a portion of patients and response correlates with dynamic adhesion profiles to MAdCAM-1. Conclusion: Our data suggest that T cell trafficking seems to be important for the pathogenesis of pouchitis and support the therapeutic use of vedolizumab. Integrin function might serve as a biomarker to predict response to vedolizumab.
CRIS-Team Scopus Importer:2021-12-17
Keywords: ileal pouch-anal anastomosis; pouchitis; proctocolectomy; T cells trafficking; vedolizumab